TÜRK HALK ANLATILARINDA GIDA KITLIĞI - Şahin, Fatma Zehra (Motif Akademi Halk Bilimi Dergisi, 2024)
Folklore products reflect information about the beliefs and practices of the society, the events experienced in the historical process, past and future designs, as well as information about the basic needs and situations of daily life. In this context, information on food and beverage culture constitutes an important area, and information on the supply, processing, protection and consumption of food reveals an experience shared in historical continuity as a cultural accumulation with its positive and negative aspects. Throughout history, people have gained important experiences as a result of the disruption of nutrition and food supply, which is one of the basic needs of people, due to different reasons. The phenomenon of famine also manifests itself in folklore products as a reflection of a common experience with its various appearances, in the sense of an experience of daily life. Folk narratives are the texts that best reflect the phenomenon of famine. The information and findings to be obtained from these texts on the subject will contribute to producing more seminal solutions to the problem of famine, which is one of the main problems of the time we live in. In this context, folk narratives were analyzed and indicators related to famine were identified. Based on these indicators, the factors causing famine are identified as climate change, soil inefficiency, wild animals, war, food waste, overconsumption and human destruction. Measures to be taken in case of famine were identified as limiting consumption, production, storage and migration. As a result, it was seen that the indicators related to the factors causing famine and the measures to be taken in case of famine were aimed at directing human attitudes and behaviors. Therefore, in Turkish folk narratives, human beings are thought to be the determining factor in the emergence and elimination of famine. In the narratives, it is fictionalized that we can make nature sustainable by turning human attitudes and behaviors in an environmentalist direction, changing them with environmentalist movements and limiting them for the environment. In this way, it is designed and conveyed that disasters such as famine do not occur, and when they do occur, they can be easily overcome.